Appropriateness and Associated Factors of Stress Ulcer Prophylaxis for Surgical Inpatients of Orthopedics Department in a Tertiary Hospital: A Cross-Sectional Study - Li, Haiyan; Li, Ning; Jia, Xiaoni; Zhai, Yuyao; Xue, Xiaorong; Qiao, Yi (Frontiers in Pharmacology, 2022)
Background: Stress ulcer prophylaxis (SUP) prescribed in patients admitted to surgical wards with low-risk of stress-related mucosal disease (SRMD) accounted for a considerable proportion of improper use of proton pump inhibitors (PPIs). This study aimed to analyze the appropriateness of SUP prescribing patterns and identify its associated factors in orthopedics department of a tertiary hospital in the Northwestern China. Methods：In this cross-sectional study, information regarding demographic and clinical characteristics of 1200 fracture inpatients who received surgical operations from January 2020 to August 2021 were collected from medical records. Established criteria were used to assess the appropriateness of prescribing pattern for SUP, and the incidence of inappropriate SUP medication was calculated. Logistic regression analyses were used to identify factors associated with inappropriate SUP medication. Results: Approximately 42.4% of the study population was interpreted as inappropriate prescription of SUP. 397 patients (33.1%) received SUP without a proper indication (overprescription), and the incidence of inappropriate SUP medication was calculated to be 43.11 per 100 patient-days. 112 inpatients (9.3%) for whom SUP was indicated didn’t receive SUP (underprescription). PPIs were prescribed in 96.1% of the inpatients who used acid suppression therapy (AST), and intravenous PPIs account for 95.3% thereof. In multivariate logistic regression analysis, older than 65 years and prolonged hospitalization were associated with overprescription of SUP. Increased number of drugs excluding PPIs, concurrent use of systemic corticosteroids, comorbidity of hypertension, unemployed and retired inpatients were associated with reduced likelihood of overprescription for SUP. Conversely, prolonged hospitalization, concurrent use of systemic corticosteroids or anticoagulants, and unemployed inpatients were positively associated with underprescription of SUP. Conclusions: There was a high prevalence of inappropriate SUP prescription among non-critically ill fracture inpatients who received surgical operations. We delineated associated factors with inappropriate SUP medication, which indicated more information needed for clinicians about rationality and efficiency of their prescribing practices. Effective intervention strategies should be executed by clinical pharmacists to reduce improper SUP medication.